BSA- and Elastin-Coated GO, but Not Collagen-Coated GO, Enhance the Biological Performance of Alginate Hydrogels - Ahmed Raslan; Laura Saenz del Burgo; Albert Espona-Noguera; Ana María Ochoa de Retana; María Luisa Sanjuán; Alberto Cañibano-Hernández; Patricia Gálvez-Martín; Jesús Ciriza; Jose Luis Pedraz (MDPI AG, 2020)
The use of embedded cells within alginate matrices is a developing technique with great clinical applications in cell-based therapies. However, one feature that needs additional investigation is the improvement of alginate-cells viability, which could be achieved by integrating other materials with alginate to improve its surface properties. In recent years, the field of nanotechnology has shown the many properties of a huge number of materials. Graphene oxide (GO), for instance, seems to be a good choice for improving alginate cell viability and functionality. We previously observed that GO, coated with fetal bovine serum (FBS) within alginate hydrogels, improves the viability of embedded myoblasts. In the current research, we aim to study several proteins, specifically bovine serum albumin (BSA), type I collagen and elastin, to discern their impact on the previously observed improvement on embedded myoblasts within alginate hydrogels containing GO coated with FBS. Thus, we describe the mechanisms of the formation of BSA, collagen and elastin protein layers on the GO surface, showing a high adsorption by BSA and elastin, and a decreasing GO impedance and capacitance. Moreover, we described a better cell viability and protein release from embedded cells within hydrogels containing protein-coated GO. We conclude that these hybrid hydrogels could provide a step forward in regenerative medicine.